Hippocampal Shape and Volume Changes with Antipsychotics in Early Stage Psychotic Illness - Mamah, Daniel; Harms, Michael P.; Barch, Deanna M.; Styner, Martin A.; Lieberman, Jeffrey; Wang, Lei (Frontiers in Psychiatry, 2012)
Progression of hippocampal shape and volume abnormalities has been described in psychotic disorders such as schizophrenia. However it is unclear how specific antipsychotic medications influence the development of hippocampal structure. We conducted a longitudinal, randomized, controlled, multisite, double-blind study involving 14 academic medical centers (United States 11, Canada 1, Netherlands 1, and England 1). 134 first-episode psychosis (receiving either haloperidol or olanzapine) patients and 51 healthy controls were treated and followed up for up to 104 weeks using magnetic resonance imaging and large-deformation high-dimensional brain mapping of the hippocampus. Changes in hippocampal volume and shape metrics (i.e., percentage of negative surface vertex slopes, and surface deformation) were evaluated. Mixed-models analysis did not show a significant group-by-time interaction for hippocampal volume. However, the cumulative distribution function of hippocampal surface vertex slopes showed a notable left shift with haloperidol treatment compared to olanzapine treatment and to controls. Olanzapine treatment was associated with a significantly lower percentage of “large magnitude” negative surface vertex slopes compared to haloperidol treatment (p=0.004). Surface deformation maps however did not localize any hippocampal regions that differentially contracted over time with olanzapine treatment, after FDR correction. These results indicate that surface analysis provides supplementary information to volumetry in detecting differential treatment effects of the hippocampus. Our results suggest that olanzapine is associated with less longitudinal hippocampal surface deformation than haloperidol, however the hippocampal regions affected appear to be variable across patients.